Synthesis of Vanillin-Azine as Colorimetric Chemosensor of Sulfide Anion - Nevi Faizatu Rokhmah; Muhammad Idham Darussalam Mardjan; Bambang Purwono (Universitas Gadjah Mada, 2022)
Vanillin-azine (VA), (4,4'-((1E,1'E)-hydrazine-1,2-diylidenebis(methane-lylidene))bis(2-methoxyphenol) has been synthesized from vanillin and tested as anion colorimetric chemosensors for sulfide anion. The VA was obtained from a condensation reaction between vanillin and hydrazine hydrate with a mol ratio of 2:1 mol for 24 h at room temperature. The structure was elucidated using FTIR, GC-MS, 1H-NMR, and 13C-NMR spectrometers. The VA compound was examined as a colorimetric chemosensor for sulfide anion over several anions of CN−, F−, Cl−, Br−, I−, N3−, CH3COO−, and NO3−. The structure of the product showed agreement with all spectrometric data. The VA chemosensor tests indicated only selective to S2− anion followed by a color change from colorless to light blue in a DMF:HEPES buffer solution (DMF:HBS) medium (9:1, v/v, 10 mM, pH = 7.4). Filter paper strips can detect S2− anion with a color change from white to yellow. The VA chemosensor has a limit of detection (LOD) of 5.4 × 10−4 M, therefore, the VA chemosensor can be applied to detect S2− anion in tap water.